Travelling Wave Solutions to Fourth-Order Nonlinear Equation - Ibrahim, Salisu (Communications in Mathematics and Applications, 2024)
In this paper, we study the soliton solutions of the fourth-order nonlinear partial differential equations (NPDE). The Riccati-Bernoulli (RB) sub-ODE method is applied to the fourth-order NPDE to investigate the exact and traveling wave solutions. We secure singular periodic wave solutions, kink-type soliton solution, dark soliton and singular soliton solution, which have unlimited application in mathematical physic, science and engineering. Some figures for the obtained solutions are demonstrated.
Keywords: Fourth-order nonlinear equation; Optical solitons; Traveling wave solutions; Riccati- Bernoulli sub-ODE method